EVALUATING THE ROLE OF AFFILIATE MARKETING AND FLASH SALES IN SHOPEE: INSIGHT THROUGH ISLAMIC ECONOMICS LAW - Nurwijayanto, Putra Ramadhani; Setyawati, Dyah; Qurrata, Vika Annisa (Universitas Airlangga, 2024)
This research investigates the influence of affiliate marketing and flash sale programs on buying interest within the Shopee Marketplace, focusing on the perspectives of Islamic Economic law among consumers at Malang City in 2024. The study employs a case study approach to examine the impact of these marketing strategies on consumer behavior and ethical considerations. Through qualitative analysis, data is gathered from Shopee users in Malang City to explore their attitudes, perceptions, and buying patterns in response to affiliate marketing and flash sale promotions. The research delves into the ethical dimensions of these marketing practices within the framework of Islamic economic principles, examining their compatibility with notions of fairness, transparency, and social responsibility in buying and selling transactions. The findings shed light on the complexities of consumer decision-making in the digital marketplace, highlighting the interplay between marketing tactics and ethical considerations rooted in Islamic economic teachings. By synthesizing insights from Islamic economic law and consumer behavior research, this study contributes to a deeper understanding of the ethical implications of modern marketing strategies in e-commerce platforms like Shopee. The research results show a significant positive influence between affiliate marketing and the flash sale program on respondents' shopping behaviour and buying interest at Shopee. Furthermore, the research provides practical implications for marketers, policymakers, and stakeholders in balancing commercial objectives with ethical standards in online retail environments.